PENERAPAN PENGGUNAAN PAPAN TULIS DIGITAL TERHADAP HASIL BELAJAR SISWA PADA OPERASI HITUNG PECAHAN DI KELAS 5C SDN KEBRAON 2 SURABAYA - Sri Rahayu (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2021)
The purpose of this classroom action research is to determine the level of effectiveness of using virtual whiteboards in online learning and also students' perceptions after using virtual whiteboards during learning. The subjects in this study were 5th grade students of SDN Kebraon 2 which consisted of all students who took part in online learning. This research is a research that uses a quantitative approach. The data used were taken from the results of the pre-test and post-test of students in working on 20 questions of fractional counting operations. The use of a digital whiteboard has an effect on increasing grades in learning fractional arithmetic operations. Based on the pre-test results that have been given, the results have increased by an average of 4.5 points. Students also feel more able to enjoy the lesson and understand the lesson more deeply.